Arabic Scrambled Card Games for Vocabulary Mastery in Islamic Schools: Permainan Kartu Acak Berbahasa Arab untuk Penguasaan Kosakata di Sekolah-Sekolah Islam - Waliyuddin, Muhammad Dzamir; Arifin, Moch. Bahak Udin By (Indonesian Journal of Islamic Studies, 2025)
General Background: Mastery of Arabic vocabulary (mufradat) is fundamental in supporting students’ proficiency in understanding, speaking, and writing Arabic, especially within Islamic educational settings. Specific Background: However, conventional teaching methods often fail to engage students, resulting in low motivation and limited vocabulary retention. Knowledge Gap: Previous studies have explored card-based learning but have not integrated visual and linguistic elements simultaneously to improve Arabic vocabulary comprehension. Aims: This study aimed to investigate the use of Arabic Scrambled Card Games in improving vocabulary mastery among eighth-grade students at Al-Fattah Buduran Middle School. Results: Using a pretest-posttest one-group experimental design with 20 participants, the study found a significant mean score increase of 32.12 points (85.37%), confirming the medium’s effectiveness in fostering vocabulary retention and comprehension. Novelty: The innovation lies in adapting Sekata cards into Arabic Scrambled cards that merge Arabic letters and images to form meaningful learning interactions. Implications: This approach enhances students’ active engagement, cognitive retention, and enjoyment in Arabic language learning, making it an effective pedagogical tool for Islamic education. Highlights: Introduces Arabic Scrambled as a novel interactive learning medium. Demonstrates significant vocabulary improvement among middle school students. Promotes engaging, meaningful Arabic learning in Islamic education contexts. Keywords: Arabic Scrambled, Mufradat, Vocabulary Learning, Islamic Education, card Games